The Historical Site of Mbah Soero Coal Mine Pit Sawahlunto, West Sumatra, as a Learning Resource for Social Science Education - Azizah, Siti Nur; Budiwirman, Budiwirman (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
The Mbah Soero Sawahlunto Coal Mine pit, located in the Segar Valley District of Sawahlunto City, West Sumatra, is one of Indonesia's historical heritage sites. It is the fifth recognized heritage site related to the coal mining industry in the country. The first coal mine in West Sumatra was discovered in Padang Sibusuk by Ir. C. De Groot, followed by the discovery of the coal around the Ombilin trunk by Ir. W.H. De Gereve. During the Dutch colonial period, coal was extracted using deep mining methods and a sandfilling system. This study aims to integrate the Mbah Soero Coal Mine Pit as a valuable learning resource in Social Science Education, specifically for junior high school students. The research employs the historical method with a qualitative descriptive approach, using data collection techniques such as literature review, observation, interviews, and documentation. Social Science Education, particularly in historical learning, is closely connected to the presence of historical sites in Indonesia, offering an engaging and interactive way for educators to teach students about their cultural heritage. The findings of this study show that incorporating the Mbah Soero Coal Mine Pit into the educational curriculum can enhance students' understanding of Indonesia's industrial history and cultural heritage. By using this site as a resource, educators can provide a richer and more engaging learning experience. In conclusion, the integration of historical sites like the Mbah Soero Coal Mine Pit into the Social Science Education curriculum offers students a deeper connection to their history, fostering awareness and appreciation of their cultural heritage. This study can serve as a reference for future research on the use of heritage sites as educational tools.